BPEL to the rescue : a real-world account the backstory of a flexible and agile application. - Wales, Robert
After spending much of last year learning to use the Business Process Execution Language (BPEL) to orchestrate Web Services and realize the benefits of a service-oriented architecture (SOA), we felt it was time for us to climb down off the bleeding edge of the razor and share our story about the real-world realities of implementing a BPEL-based project.